A Novel Bifunctional Amino Acid Racemase With Multiple Substrate Specificity, MalY From Lactobacillus sakei LT-13: Genome-Based Identification and Enzymological Characterization - Kato, Shiro; Oikawa, Tadao (Frontiers in Microbiology, 2018)
The Lactobacillus sakei strain LK-145 isolated from Moto, a starter of sake, produces potentially large amounts of three D-amino acids, D-Ala, D-Glu and D-Asp, in a medium containing amylase digested rice as a carbon source. 　The comparison of metabolic pathways deduced from the complete genome sequence of strain LK-145 to the type culture strain of Lactobacillus sakei strain LT-13 showed that the L- and D-amino acid metabolic pathways are similar between the two strains. However, a marked difference was observed in the putative cysteine/methionine metabolic pathways of strain LK-145 and LT-13. The cystathionine -lyase homolog gene malY was annotated only in the genome of strain LT-13. Cystathionine -lyase is an important enzyme in the cysteine/methionine metabolic pathway that catalyzes the conversion of L-cystathionine into L-homocysteine. In addition to malY, most genome-sequenced strains of L. sakei including LT-13 lacked the homologous genes encoding other putative enzymes in this pathway. 　Accordingly, the cysteine/methionine metabolic pathway likely does not function well in almost all strains of L. sakei. We succeeded in cloning and expressing the malY gene from strain LT-13 (Ls-malY) in the cells of Escherichia coli BL21 (DE3) and characterized the enzymological properties of Ls-MalY. Spectral analysis of purified Ls-MalY showed that Ls-MalY contained a pyridoxal 5-phosphate (PLP) as a cofactor, and this observation agreed well with the prediction based on its primary structure. Ls-MalY showed amino acid racemase activity and cystathionine -lyase activity. Ls-MalY showed amino acid racemase activities in various amino acids, such as Ala, Arg, Asn, Glu, Gln, His, Leu, Lys, Met, Ser, Thr, Trp, and Val. Mutational analysis revealed that the -amino group of Lys233 in the primary structure of Ls-MalY likely bound to PLP, and Lys233 was an essential residue for Ls-MalY to catalyze both the amino acid racemase and -lyase reactions. In addition, Tyr123 was a catalytic residue in the amino acid racemase reaction but strongly affected -lyase activity. These results showed that Ls-MalY is a novel bifunctional amino acid racemase with multiple substrate specificity; both the amino acid racemase and -lyase reactions of Ls-MalY were catalyzed at the same active site.